Nanotechnological synergy of mangiferin and curcumin in modulating PI3K/Akt/mTOR pathway: a novel front in ovarian cancer precision therapeutics - Hanan M. Alharbi; Taha Alqahtani; Ali H. Alamri; Vinoth Kumarasamy; Vetriselvan Subramaniyan; Vetriselvan Subramaniyan; K. Suresh Babu (Frontiers Media S.A., 2024)
Background: Ovarian cancer, colloquially termed the "silent killer" among gynecological malignancies, remains elusive due to its often-asymptomatic progression and diagnostic challenges. Central to its pathogenesis is the overactive PI3K/Akt/mTOR signaling pathway, responsible for various cellular functions, from proliferation to survival. Within this context, the phytochemical compounds mangiferin (derived from Mangifera indica) and curcumin (from Curcuma longa) stand out for their potential modulatory effects. However, their inherent bioavailability challenges necessitate innovative delivery systems to maximize therapeutic benefits.Objective: This study seeks to synergize the merits of nanotechnology with the therapeutic properties of mangiferin and curcumin, aiming to bolster their efficacy against ovarian cancer.Methods: Employing specific nanotechnological principles, we engineered exosomal and liposomal nano-carriers for mangiferin and curcumin, targeting the PI3K/Akt/mTOR pathway. Molecular docking techniques mapped the interactions of these phytochemicals with key proteins in the pathway, analyzing their binding efficiencies. Furthermore, molecular dynamics simulations, spanning 100 nanoseconds, verified these interactions, with additional computational methodologies further validating our findings. The rationale for the 100 nanoseconds time span lies in its sufficiency to observe meaningful protein-ligand interactions and conformational changes. Notably, liposomal technology provided an enhancement in drug delivery by protecting these compounds from degradation, allowing controlled release, and improving cellular uptake.Results: Our computational investigations demonstrated notable binding affinities of mangiferin and curcumin: PI3K at −11.20 kcal/mol, Akt at −15.16 kcal/mol, and mTOR at −10.24 kcal/mol. The adoption of exosome/liposome-mediated delivery significantly amplified the bioavailability and cellular uptake of these nano-formulated compounds, positioning them as potential stalwarts in ovarian cancer intervention. A brief explanation of exosome/liposome-mediated delivery involves the use of these vesicles to encapsulate and transport therapeutic agents directly to the target cells, enhancing drug delivery efficiency and minimizing side effects.Conclusion: Addressing ovarian cancer's intricacies, dominated by the erratic PI3K/Akt/mTOR signaling, mandates innovative therapeutic strategies. Our pioneering approach converges nanotechnological liposomal delivery with mangiferin and curcumin's natural efficacies. This confluence, validated by computational insights, heralds a paradigm shift in ovarian cancer treatment. As our findings underscore the collaborative potential of these phytochemicals, it beckons further exploration in translational studies and clinical applications, ensuring the best intersection of nature and technology for therapeutic advantage.